2018
DOI: 10.1016/j.biopha.2018.05.108
|View full text |Cite
|
Sign up to set email alerts
|

Dangguishaoyao-San attenuates LPS-induced neuroinflammation via the TLRs/NF-κB signaling pathway

Abstract: This study demonstrated that DSS has a protective effect on neuroinflammation in LPS-induced BV-2 microglia cells through the TLRs/NF-κB signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Subsequently, the free NF-κB dimer translocates to the nucleus and promoting the transcription of various pro-inflammatory enzymes (Mercurio and Manning, 1999;Ghosh and Hayden, 2008;Lappas et al, 2002;Ren et al, 2019;Cai et al, 2018). Many studies have found that inhibition of NF-ĸB pathway can effectively reduce LPS-induced inflammation (Fu et al, 2018;Ding et al, 2018). In this study, we also found that the expression of phosphorylated IκB and NF-κB were remarkably upregulated in LPS-stimulated group, which are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, the free NF-κB dimer translocates to the nucleus and promoting the transcription of various pro-inflammatory enzymes (Mercurio and Manning, 1999;Ghosh and Hayden, 2008;Lappas et al, 2002;Ren et al, 2019;Cai et al, 2018). Many studies have found that inhibition of NF-ĸB pathway can effectively reduce LPS-induced inflammation (Fu et al, 2018;Ding et al, 2018). In this study, we also found that the expression of phosphorylated IκB and NF-κB were remarkably upregulated in LPS-stimulated group, which are consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…The anti-inflammatory activity of the extracts was evaluated pretreating BV-2 cells with different concentrations (1-100 μ g mL −1 ) of the extracts for 24 h before exposing the cells to lipopolysaccharide (LPS) to induce inflammation ( Figure 8 ). LPS is the most widely used inflammatory mediator to activate microglial cells in vitro and triggers the proinflammatory signaling cascade [ 78 , 79 ]. LPS treatment significantly reduced cell viability with respect to control cells by ~40%.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 illustrated that lots of compounds in DSS act on the targets of NF-ĸB signaling pathway, indicating the potential AD therapeutic mechanism mediated by DSS. Recent in vitro study showed that DSS has a protective effect on neuroinflammation in lipopolysaccharide (LPS)-stimulated BV-2 microglia cells through the TLRs/NF-κB signaling pathway [ 61 ].…”
Section: Resultsmentioning
confidence: 99%